If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -6) = 52 Reorder the terms: 4(-6 + x) = 52 (-6 * 4 + x * 4) = 52 (-24 + 4x) = 52 Solving -24 + 4x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 4x = 52 + 24 Combine like terms: -24 + 24 = 0 0 + 4x = 52 + 24 4x = 52 + 24 Combine like terms: 52 + 24 = 76 4x = 76 Divide each side by '4'. x = 19 Simplifying x = 19
| 24=(2x)-(3x-1) | | 0.8x=0.16 | | 1.5x^2+3x-12=0 | | -3(a+5)-10(1-6a)= | | 11x+8=1x+48 | | 6(a-2b)-3(2a+b)= | | 0.16xn=74 | | (7x+6)-(-8x+9)= | | -2x-13=6 | | 3.5x(2x+3)-3x(x+1.5)= | | 1000z^3-1=0 | | 6-5p=-7p+3p | | 3(-2-3x)=-8x-4 | | y+0.4=0.6y+1.2 | | -128-8y=-48 | | 5n^2+5n=6 | | 5w=-5w+10w | | 2v^2-11v=v^2-14 | | 3(a-7)=21 | | 770=22w | | -20=x+7 | | 8x-9=2x+3 | | (6x+4)-(8x+8)= | | 0.7n-9+3=11-0.3n-15 | | 4g-3=-10 | | 0.5x+3=9.5 | | -4x^2-22x-10= | | 14+12x=11x-38 | | 11b=143 | | -4x-22x-10= | | 120=(2x+10)+(x+15) | | 7d+5=17.25 |